Anisakis spp. as indicators of latitudinal movements of short‐finned pilot whales, Globicephala macrorhynchus , in the Northeast Atlantic - Claudia Pons‐Bordas; Rachel V. Pool; Sofía Ten; José A. Armenteros‐Santos; Ana Balseiro; Manena Fayos; F. Javier Aznar (Marine Mammal Science, 2025)
In the Northeast Atlantic, it is unclear whether short‐finned pilot whales, Globicephala macrorhynchus (SFPWs), are transient or resident above 40°N. We used Anisakis spp. to identify the latitudes recently visited by a SFPW pod stranded in NW Spain (43°N) in 2020. Analysis of cox2 gene in 30 nematodes from 6 SFPWs revealed the presence of A. simplex sensu stricto (s.s.) (93.3%) and A. pegreffii (6.7%). Morphological analysis of 972 nematodes corroborated species molecular identification and relative proportions; in males ( n = 66), the estimated proportions of A. simplex s.s. and A. pegreffii were 86.4% and 13.6%, respectively. These percentages resembled those reported in fish/cetaceans above 40°N, and L4 larvae or adults of A. typica (a tropical‐temperate species found in SFPWs up to 38°N–39°N) were not detected. Population structure of A. simplex s.s. + A. pegreffii in SFPWs suggested a continuous recruitment of nematodes starting at least 3 weeks before stranding. We interpret that either the SFPW pod was within the range of the species (perhaps as a recent northern shift) or represented a vagrant group that visited waters off Northwest Spain for a protracted period. Future analysis on nematode assemblages could shed light on movements and climate‐driven shifts in cetacean distribution.

The contribution of fish to the diet of loggerhead sea turtles in the western Mediterranean revisited - Luis Cardona; F. Javier Aznar; Maria Bas; Jesús Tomás (Marine Biology, 2024)
Early juvenile loggerhead turtles ( Caretta caretta ) rely on gelatinous zooplankton, whereas individuals larger than 40 cm curved carapace length are adapted to crush hard-shelled invertebrates. Nevertheless, fish were reported to be the staple food of loggerhead turtles in the western Mediterranean 30 years ago. Here, the temporal consistency of such a fish-based diet of loggerhead turtles is assessed through gut content analysis and stable isotope analysis of samples from the Mediterranean coast of Spain spanning three decades. The gut contents of 134 juvenile loggerhead turtles (curved carapace length range: 27–71 cm) from three different periods (1991, 1999–2008 and 2010–2017) were analyzed, as well as a subsample of the same turtles ( n = 10 in each period) for both bulk and compound-specific stable isotope ratios (CSIA-AA). Gut content analysis revealed a decline in the frequency of occurrence and numerical abundance of fish and an increasing contribution of gastropods and bivalves throughout time, although pelagic tunicates were always the most frequently observed prey. The δ 15 N bulk of turtle bone also dropped throughout the study period, but the values of the stable isotope ratio of N in phenylalanine (δ 15 N Phe ) indicated that 52.5% of that variability was due to a baseline shift over time. Accordingly, the trophic position estimated from CSIA-AA did not follow the decreasing pattern of δ 15 N bulk , but fluctuated throughout time. The overall evidence indicates that fish consumption by loggerhead turtles in the study region declined through time, but the trophic position of loggerhead turtles did not change simultaneously. This is probably because low trophic prey such pelagic tunicates and filter-feeding bivalves and suspension-feeding gastropods were the bulk of the diet during the whole study period and fish played a minor role, even when their frequency of occurrence peaked. Past levels of high fish consumption might be due to high levels of fishery discards, currently declining because of the recent reduction of the fishing fleet.